Synthetic Mimotopes of Salivary Peptides against SARS-CoV-2 In Vitro - Garcia-Júnior, M.A.; Grosche, V.R.; Palmeira, L.S.; Teles, C.; Ferreira, G.M.; Martins, D.O.S.; Guevara-Vega, M.; Carneiro, M.G.; Abuna, R.P.F.; Martins, M.M.; Rahal, P. [UNESP]; da Silva, J.S.; et al. (SAGE Publications, 2025)
To replicate, SARS-CoV-2 requires its receptor-binding domain (RBD) motif in the Spike protein to interact with specific cellular receptors, such as angiotensin-converting enzyme 2 (ACE2), in human cells. Hence, we aimed to select high-affinity naturally expressed salivary peptides by bioinformatics to assess their potential to block the Spike-RBD/ACE2 interaction in vitro and to evaluate their SARS-CoV-2 antiviral performance. We designed a pipeline with 2,193 salivary peptides and performed molecular docking with 298 peptides using BLASTp. In silico molecular docking was evaluated using HPEPDOCK and validated by molecular dynamics with GROMACS-2020.3 against crystallographed Wuhan wild-type SARS-CoV-2 (SARS-CoV-2WT) Spike-RBD, and the 4 best-performing peptides were redocked against Gamma, Delta, and Omicron Spike-RBD. These 4 selected peptides were synthesized, and antiviral activity was evaluated using VSV-eGFP-SARS-CoV-2 pseudotyped virus and SARS-CoV-2WT. Finally, we evaluated the inhibition of cell death in SARS-CoV-2WT and viral replication inhibition of Gamma and Omicron variants by synthetic mimotopes of salivary peptides by quantifying viral titers using reverse transcription quantitative polymerase chain reaction (RT-qPCR). Salivary peptides SalivaPep1, SalivaPep2, SalivaPep3, and SalivaPep4 had higher binding energy to SARS-CoV-2WT-Spike-RBD, and their effects were maintained against variants, suggesting salivary peptide interactions with SARS-CoV-2. The VSV-eGFP-SARS-CoV-2 infection inhibition rates of selected salivary peptides ranged from 67.5% to 37.6%, respectively, at about 100% cell viability. SalivaPep1, SalivaPep2, and SalivaPep3 reduced cell death resulting from viral replication against SARS-CoV-2WT. Lastly, RT-qPCR showed up to a 74.9% decrease in viral copies against the Gamma variant and 62.5% against the Omicron variant by the treatment with SalivaPep3 and SalivaPep2, derived from salivary Ataxin-1 and Statherin, respectively. The presented bioinformatics workflow was profitable to select on-demand naturally occurring salivary peptides with confirmed antiviral properties in SARS-CoV-2WT, Gamma, and Omicron variants by synthetic mimotopes of salivary peptides, with potential application to prophylactic, diagnostic and therapeutic strategies toward COVID-19.